Lower Performance in Orientation to Time and Place Associates with Greater Risk of Cardiovascular Events and Mortality in the Oldest Old: Leiden 85-Plus Study - Rostamian, Somayeh; van Buchem, Mark A.; Jukema, J. Wouter; Gussekloo, Jacobijn; Poortvliet, Rosalinde K. E.; de Cren, Anton J. M.; Sabayan, Behnam (Frontiers in Aging Neuroscience, 2017)
Abstract Background: Impairment in orientation to time and place is commonly observed in community-dwelling older individuals. Nevertheless, the clinical significance of this has been not fully explored. In this study, we investigated the link between performance in orientation domains and future risk of cardiovascular events and mortality in a non-hospital setting of the oldest old adults. Methods: We included 528 subjects free of myocardial infarction, 477 individuals free of stroke/transient ischemic attack, and 432 subjects free of both myocardial infarction and stroke/transient ischemic attack at baseline from the population-based Leiden 85-plus cohort study. Participants were asked to answer five questions related to orientation to time and five questions related to orientation to place. 5-year risks of first-time fatal and non-fatal myocardial infarction, fatal and non-fatal stroke, as well as cardiovascular and non-cardiovascular mortality, were estimated using the multivariate Cox regression analysis. Results: In the multivariable analyses, adjusted for sociodemographic characteristics and cardiovascular risk factors, each point lower performance in ‘orientation to time’ was significantly associated with higher risk of first-time myocardial infarction (hazard ratio [HR] 1.35, 95%confidence interval [CI] 1.09-1.67, p=0.007), first-time stroke (HR 1.35, 95%CI 1.12-1.64, p=0.002), cardiovascular mortality (HR 1.28, 95%CI 1.06-1.54, p=0.009) and non-cardiovascular mortality (HR 1.37, 95%CI 1.20-1.56, p<0.001). Similarly, each point lower performance in ‘orientation to place’ was significantly associated with higher risk of first-time myocardial infarction (HR 1.67, 95%CI 1.25-2.22, p=0.001), first-time stroke (HR 1.39, 95%CI 1.05-1.82, p=0.016), cardiovascular mortality (HR 1.35, 95%CI 1.00-1.82, p=0.054) and non-cardiovascular mortality (HR 1.45, 95%CI 1.20-1.77, p<0.001). Conclusions: Lower performance in orientation to time and place in advanced age is independently related to higher risk of myocardial infarction, stroke and mortality. Impaired orientation might be an early sign of covert vascular injuries, putting subjects at greater risk of cardiovascular events and mortality.